Substitution Urethroplasty With Buccal Mucosal Graft in the Management of Stricture of Vesicourethral Anastomosis or Membranous Urethra: Single-institution Long-term Experience With Perineal Approach and Endourethroplasty - Doležel, Jan; Hrabec, Roman; Uher, Michal; Čapák, Ivo; Šebová, Natália; Staník, Michal (Urology, 2024)
OBJECTIVE: To present long-term experience with buccal mucosa posterior urethroplasty (BMPU) for refractory posterior urethral stenosis (PUS) or vesicourethral anastomosis stenosis (VUAS) either by perineal approach (PA) or by endourethroplasty (EUP). MATERIALS AND METHODS: A single-center retrospective study of 38 consecutive patients operated on between 1999 and 2022. BMPU consisted of the transfer of onlay or tubular buccal mucosa grafts into dilated and/or incised strictures through an open or endourological approach. If VUAS or PUS recurred with short stenosis within the first 12 months after surgery, it was transected by a cold-knife direct vision internal urethrotomy (DVIU), referred to as an "auxiliary" DVIU. The primary outcome was 3-year stricture recurrence-free survival (SRFS). RESULTS: BMPU by perineal approach and EUP were performed in 27 (71%) and 11 (29%) patients, respectively. The 3-year SRFS was 65% for the whole cohort, with rates of 63% for the perineal approach and 73% for endourological approach. With permitted auxiliary DVIU, 3-year SRFS for the whole cohort was 81%. De novo incontinence occurred in 2 out of 18 preoperatively continent patients. Limitations include the retrospective nature of the single-center study and a small, heterogenous cohort of patients. CONCLUSION: We present 2 techniques of substitution urethroplasty with BMG in the management of PUS and VUAS with a low rate of recurrence or de novo incontinence. A novel endourological approach (EUP) is a promising minimally invasive alternative to the perineal approach.
Keywords: dospělí; Plastic Surgery Procedures; Adult; striktura uretry; výsledek terapie; mladý dospělý; Adolescent; Time Factors; časové faktory; Urethra; lidé; anastomóza chirurgická; uretra; Mouth Mucosa; Treatment Outcome; Urethral Stricture; zákroky plastické chirurgie; perineum; retrospektivní studie; urologické chirurgické výkony u mužů; Male; ústní sliznice; Aged; Anastomosis, Surgical; Urinary Bladder; močový měchýř; Urologic Surgical Procedures, Male; Perineum; Young Adult; lidé středního věku; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; mladiství; Humans